Radioimmunoassay of Human Serum Thyrotrophin. Issue 5749 (13th March 1971) - Hall, Reginald; Amos, Jacqueline; Ormston, Brian J.
Abstract : The double antibody radioimmunoassay of serum thyroid-stimulating hormone (TSH) allows measurement of circulating levels of the hormone in most normal subjects. The serum TSH level in normal subjects is 1·6 ± 0·8μU/ml. Patients with non-toxic goitre and acromegaly have normal TSH levels. Values are always raised in hypothyroid patients (with primary thyroid disease) and are significantly lowered in those with hyperthyroidism. Of the many stimuli used in an attempt to raise TSH levels in normal adult subjects only three—synthetic thyrotrophin-releasing hormone, ethinyloestradiol, and carbimazole plus iodides—have been effective. The major clinical application of the TSH immunoassay lies in the diagnosis of minor degrees of hypothyroidism. An impaired response of serum TSH to synthetic thyrotrophin-releasing hormone should also help in the diagnosis of hypopituitarism affecting TSH production.